Awad M. Abdel-Rahim - Abdel-Rahim, Awad M.; Bashiar, Hadia A. M.; Sulieman, Abdel-Moneim A. (Gezira Journal of Engineering and Applied Sciences, 2012)
Many plants were found to synthesize substances that are useful to the maintenance of health in humans and animals. Romman, pomegranate (Punica grantum) has been reported to have some antimicrobial activity. The present study was aiming to investigate the antifungal and antibacterial properties of the Romman fruit peel and flower extracts. The radial growth and the dry weight methods were used for fungi, while, the plate count and the inhibition zone methods were used for bacteria. Both fruit peel and the flower were found to contain high amounts of tannins.  The study showed that the extracts were effectively inhibited mycelial growth and dry weight of both Aspergillus niger and Penicillium italicum . However, the effect was only significant at the higher concentration. On the other hand, the extracts of the fruit peel were highly effective against bacteria. It inhibited growth of both Gram-positive ( Staphylococcus aureus ) and Gram- negative ( E. coli ) bacteria, although, the effect was more pronounced on the Gram- negative bacteria.